Microbiota-derived indole acetic acid extends lifespan through the AhR-Sirt2 pathway in Drosophila - Zheng Cao; Cui Zhang; Lijun Liu; Hehua Lei; Huabao Zhang; Yanmeng He; Xinzhi Li; Qingwei Xiang; Yu-Feng Wang; Limin Zhang; Gang Chen (mSystems)
ABSTRACT Disruption of aryl hydrocarbon receptor (AhR) signaling and aberrant tryptophan metabolism have been shown to be highly associated with aging and age-related disorders. However, the underlying molecular mechanisms by which the AhR-mediated signaling pathway contributes to the aging process remain largely unknown. In this study, we find that aged Drosophila exhibits markedly reduced tryptophan metabolism leading to impaired AhR ligands, especially indole acetic acid (IAA), compared with their young controls. Supplementation with IAA, produced from Lactobacillus spp., dose-dependently extends the lifespan of Drosophila and improves healthy aging with resistance to starvation and oxidative stress. Mechanistically, activation of AhR by IAA markedly enhances Sirt2 activity by binding to its promoter, thereby inhibiting downstream TOR signaling and related fatty acid and amino acid metabolism. Both Ahr and Sirt2 mutant flies with IAA supplementation display a negligible lifespan extension, suggesting that AhR-mediated Sirt2 signaling contributes to lifespan extension in flies upon IAA supplementation. From the perspective of host metabolism, IAA supplementation significantly increases unsaturated fatty acids (UFAs) in aged flies, which are regarded to be beneficial for healthy status. These findings provide new insights into the physiological functions of AhR involved in the aging process by mediating Sirt2 signaling.IMPORTANCEDisruption of aryl hydrocarbon receptor (AhR) signaling and aberrant tryptophan metabolism contribute to aging and age-related disorders, but the underlying molecular mechanisms are largely unknown. Using multiomics analyses combined with biochemical assays, this study reveals that AhR activation by indole acetic acid (IAA) effectively extends the lifespan accompanied by improved healthy aging in Drosophila via the AhR-Sirt2 pathway.